Fatty acid composition of breast and thigh muscles of broilers fed diets supplemented with candle nut kernel meal subjected to different heat treatments - Rohaida, A.R. (2016)
An experiment was conducted to determine the effects of heat treated candlenut kernel meal (CNKM) supplementation in broiler diet on fatty acid profiles in breast and thigh muscle of broiler chickens at grower-finisher stage. A total of 270 male broiler chickens (Cobb500), 21 days of age , were given six dietary treatments (control, control supplemented with unheated, oven-heated, roasted, boiled, and autoclaved ground candlenut kernel meal). Feed intake and body weight were measured over three weeks. There were no significant effects of different types of heat treatment on the chemical composition of CNKM. However, there were significant differences on the saponin content, in which roasted, boiled and autoclaved CNKM had significantly lower (p<0.05) saponin than untreated or oven-heated CNKM. Fatty acid composition of CNKM was not significantly affected by the heat treatment for some fatty acids. Birds fed diets supplemented with autoclaved candlenut meal showed the highest growth rate amongst the treatments. In conclusion, supplementing either treated or untreated candlenut meal at 2% level in broiler diet increased the omega-3 fatty acids, and the presence of saponin in the diet due to CNKM had no major influence on meat fatty acid profiles.